DIDACTIC REQUIREMENTS FOR THE FORMATION OF STEAM COMPETENCIES IN TEACHING NATURAL SCIENCES IN ELEMENTARY GRADES - Madina Xaydarova Baxodirjon’s daughter (Bright Mind Publishing, 2025)
This study examines the didactic requirements necessary for the effective formation of STEAM (Science, Technology, Engineering, Arts, and Mathematics) competencies in the teaching of natural sciences to elementary school students. Expert validation confirmed the relevance and feasibility of the proposed didactic requirements, emphasizing the need for tiered scaffolding and expanded use of digital tools. Guided by a mixed-methods research design, the study combined theoretical analysis of educational literature and curriculum standards with an empirical intervention in three public schools involving 120 students and 15 teachers. The study concludes that a systematically designed and contextually adapted didactic framework can substantially enhance STEAM competency development in early science education, with implications for curriculum design, teacher training, and sustainable implementation in primary schools.
Keywords: STEAM education, didactic requirements, natural science teaching, elementary grades, competency-based learning, inquiry-based learning, design thinking, arts integration, interdisciplinary approach, primary education pedagogy, collaborative learning, educational innovation.